PENDOKUMENTASIAN ASUHAN KEPERAWATAN DITINJAU DARI BEBAN KERJA PERAWAT - Supratman Supratman; Yuni Wulan Utami (Jurnal Berita Ilmu Keperawatan, 2009)
Level of ratio of nurse’s-patient in RSDM initiation to prove with the research. Research questions: 'whether at workload of nurse’s become the factor influencing to lower the execution of documentation of nursing care in RSDM?'. Research wish to know how execution of documentation of nursing care in RSDM between nurse’s which its workload is heavy and nurse which its workload is light. Research design use the crosssectional by sample as much 32 one who is taken by consecutive. Research conducted in four unit take care of to lodge the RSDM Surakarta of four month; July-September 2006. Total workload measurement use the technique of semi-structure interview of where respondent reply some opened semi question and given by the opportunity to submit the opinion of concerning their work. Approach of measurement of workload referred the concept Ilyas (2000), that is combination of ‘work sampling’ and ‘daily log’. Analyze the data aim to make the inference with the tables 2x2 to measure the Ratio Prevalence (RP) and Confident Interval 95% (CI95%) with the alpha level 5% (α=5%). Result of research is in general known that by the heavy workload still be experienced by most nurse’s in RSDM. Type of workload which relative heavily stem from nursing care (treatment) work directly. Workload of nurse become the its low risk factor is execution of documentation of nursing care in RSDM. Even with the downhill heavier workload hence it documentation execution own the opportunity 10,7 times (OR=10.7).